Penerapan Metode Demonstrasi untuk Meningkatkan Keterampilan Siswa Menyolatkan Jenazah di Kelas XI MIA 2 SMT Genap SMA Negeri 3 Bengkalis Tahun Pelajaran 2018/2019 - - Syarifah (Akademika: Jurnal Keagamaan dan Pendidikan, 2019)
As a Muslim, the law for passing the corpse is fardhu kifayah. In class XI MIA 2, the total number of students was 22 people consisting of 4 Buddhists, while 18 were Muslims. From the 18 students, 11 (61.1%) students were passed the grade and 7 (38.9%) students were not passed the grade for completing the bodies. Some of the students cannot understand about the vow and cannot memorized well how to praying the bodies. In this research, the writer did 2 cycles and used demonstration method. The result of the research from the cycle 1, 77.8 % students passed the grade to praying bodies and 22.2 % still incomplete to praying the bodies. On cycle 2, 88.9 % students passed the grade to praying the bodies and 11.1 % cannot pray the bodies yet.